¿Cómo percibieron el covid-19 los alumnos de educación primaria?: Una mirada a través del dibujo infantil = Abweichender Titel: How did Primary School students Perceive Covid-19? : A Look through Children's Drawings - Díez Fernández, Pelayo (Cauriensia, 2025)
COVID-19 has drastically changed the way of life for human beings, and more specifically for the youngest, depriving them of many key experiences for their socio-emotional development. The objective of this study is to analyze primary school students' perceptions of the lockdown imposed during the 2020 pandemic. In this way, great visibility has been given to a vulnerable and often unheard group. From a methodological perspective, a content analysis will be carried out using children's drawings as a data collection tool, allowing us to understand how children have identified this phenomenon. A total of 66 drawings were collected, which revealed that some of the most common restrictive measures were confinement, mobility restrictions, and the use of face masks as a preventive measure. This circumstance has led students to adapt to and engage in new learning experiences. Considering all the above, the work presented here demonstrates how drawing is a powerful tool for understanding how students can express and identify what they feel in a simple and natural way.